THE IMPORTANCE OF THE PONTIFICATE OF THE POPE JOHN PAUL II IN INTERNATIONAL RELATIONS - Azevedo, M. Manuel (UI Scholars Hub, 2024)
This work analyses Pope John Paul II’s contributions and attitudes as an international relations Actor. In this context, the research question that guides this work is as follows in terms of global governance, how did the conduct carried out by Pope John Paul II strengthen him as a Model Power? John Paul II inaugurated a new phase of the Vatican’s foreign policy. His diplomacy in mediation and conflict resolution stands out as a fundamental pillar of his pontificate, contributing to the fall of the communist regime in Poland and many other conflicts such as the mediation of the Holy See in the Beagle Channel, Falklands War, Gulf Wars and Balkan War. In the religious dominion, John Paul II intensified inter-religious dialogue with Jewish, Muslim and Buddhists. Regarding Papal trips, they played an extremely relevant role not only from a religious perspective but also from a political and social perspective. Protecting the environment and life was also among John Paul II’s concerns. The Pope clarified that the Church cannot be indifferent to how humans relate to nature. In summary, the words of John Paul II had a significant impact on the political world and civil society, with him being considered a great statesman of the 20th century; in this sense, he could be viewed as a relevant actor in international relations and a Model Power.